+0  
 
0
37
1
avatar+559 

Find $a+b+c$, given that $x+y\neq -1$ and \begin{align*} ax+by+c&=x+7,\\ a+bx+cy&=2x+6y,\\ ay+b+cx&=4x+y. \end{align*}

supermanaccz  Mar 30, 2018

Best Answer 

 #1
avatar+6943 
+2

Find  \(a+b+c\) , given that  \(x+y\neq -1\)  and  \( \begin{align*} ax+by+c&=x+7,\\ a+bx+cy&=2x+6y,\\ ay+b+cx&=4x+y. \end{align*}\)

 

-----------------------------------------------------------------------------------------------------------------------

 

(ax + by + c) + (a + bx + cy) + (ay + b + cx)  =  (ax + by + c) + (a + bx + cy) + (ay + b + cx)

 

(ax + by + c) + (a + bx + cy) + (ay + b + cx)  =  (x + 7) + (2x + 6y) + (4x + y)

 

ax + by + c + a + bx + cy + ay + b + cx  =  x + 7 + 2x + 6y + 4x + y

 

ax + bx + cx + ay + by + cy + a + b + c  =  7x + 7y + 7

 

x(a + b + c) + y(a + b + c) + 1(a + b + c)  =  7(x + y + 1)

 

(a + b + c)(x + y + 1)  =  7( x + y + 1)

 

a + b + c  =  7

hectictar  Mar 30, 2018
edited by hectictar  Mar 30, 2018
Sort: 

1+0 Answers

 #1
avatar+6943 
+2
Best Answer

Find  \(a+b+c\) , given that  \(x+y\neq -1\)  and  \( \begin{align*} ax+by+c&=x+7,\\ a+bx+cy&=2x+6y,\\ ay+b+cx&=4x+y. \end{align*}\)

 

-----------------------------------------------------------------------------------------------------------------------

 

(ax + by + c) + (a + bx + cy) + (ay + b + cx)  =  (ax + by + c) + (a + bx + cy) + (ay + b + cx)

 

(ax + by + c) + (a + bx + cy) + (ay + b + cx)  =  (x + 7) + (2x + 6y) + (4x + y)

 

ax + by + c + a + bx + cy + ay + b + cx  =  x + 7 + 2x + 6y + 4x + y

 

ax + bx + cx + ay + by + cy + a + b + c  =  7x + 7y + 7

 

x(a + b + c) + y(a + b + c) + 1(a + b + c)  =  7(x + y + 1)

 

(a + b + c)(x + y + 1)  =  7( x + y + 1)

 

a + b + c  =  7

hectictar  Mar 30, 2018
edited by hectictar  Mar 30, 2018

13 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details